2022
DOI: 10.3390/ijms23052684
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Roles for Cytokines in Atopic Dermatitis: From Pathogenic Mediators to Endotype-Specific Biomarkers to Therapeutic Targets

Abstract: Atopic dermatitis (AD) is one of the most common chronic inflammatory skin diseases, which generally presents with intense itching and recurrent eczematous lesions. AD affects up to 20% of children and 10% of adults in high-income countries. The prevalence and incidence of AD have increased in recent years. The onset of AD mostly occurs in childhood, although in some cases AD may persist in adult life or even manifest in middle age (adult-onset AD). AD pathophysiology is made of a complex net, in which genetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(54 citation statements)
references
References 129 publications
(169 reference statements)
2
52
0
Order By: Relevance
“…[28][29][30] Furthermore, previous studies correlated IL-22 and S100A gene expression levels in skin with AD clinical severity and decreased expression was correlated with clinical therapeutic response 31 ; IL-22 expression is also correlated with epidermal hyperplasia, and reduced IL-22 levels may result in reduction in epidermal thickness. 32 Findings from this study were consistent with the efficacy profile of abrocitinib; reduced expression of S100A genes was correlated with itch improvement and skin clearance. Future studies could explore whether the reduction in epidermal thickness observed in abrocitinib-treated patients is correlated with the abrocitinib-mediated reduction of IL-22 and S100A gene expression levels.…”
Section: Discussionsupporting
confidence: 80%
“…[28][29][30] Furthermore, previous studies correlated IL-22 and S100A gene expression levels in skin with AD clinical severity and decreased expression was correlated with clinical therapeutic response 31 ; IL-22 expression is also correlated with epidermal hyperplasia, and reduced IL-22 levels may result in reduction in epidermal thickness. 32 Findings from this study were consistent with the efficacy profile of abrocitinib; reduced expression of S100A genes was correlated with itch improvement and skin clearance. Future studies could explore whether the reduction in epidermal thickness observed in abrocitinib-treated patients is correlated with the abrocitinib-mediated reduction of IL-22 and S100A gene expression levels.…”
Section: Discussionsupporting
confidence: 80%
“…Even though one disease may be multifactorial, targeting only one pivotal pathway may already be effective. One example is atopic dermatitis, of which the pathogenesis is multifactorial, [57][58][59] with the JAK-STAT pathway being one of the pathways that may be targeted. 24 For this indication, JAK inhibitors as monotherapy are now part of the treatment regimen in many countries.…”
Section: Limitationsmentioning
confidence: 99%
“…Immune system dysregulation, mainly in the expression of type 2 chemokines, such as IL-14 and IL 13, leads to the suppression of antimicrobial peptides and allergic inflammation [58,59]. IL-31 is linked to the induction of itching in patients with AD, by producing a brain-derived natriuretic peptide and coordinating chemokine release from skin cells [60,61].…”
Section: The Pathophysiology Of Atopic Dermatitis and The Role Of Wat...mentioning
confidence: 99%